Effects of ensiling period and lactic acid bacteria inoculation on aerobic stability of silage in forage infected with leaf spot disease - Tang, Guojian; Yang, Jinmei; Meng, Yuanyan; Zhang, Xiaolong; Wen, Mengxin; Sun, Ting; Wu, Dan; Xu, Liuxing (Frontiers in Microbiology, 2025)
When forage crops are ravaged by leaf spot disease, producers face an unavoidable dilemma: a careful consideration of adopting specific measures to make use of the damaged forage. Furthermore, silage is often exposed to air during production, feeding, storage, and transportation. The aim of this study is to investigate the effects of three ensiling periods (15, 30, and 60 days), two crops (Italian ryegrass, and oats), and three additives [control group (CK), inoculated with Lactobacillus plantarum YM3, and L. rhamnosus HT1] on the health and fermentation quality of silage infected with leaf spot disease during aerobic exposure. Silage ensiled for 15 days had the highest lactic acid concentration and the lowest butyric acid concentration (p < 0.05). The acetic acid concentration of Italian ryegrass silage (5.77 g kg−1 DM) was higher than that of oat silage (2.89 g kg−1 DM), and the butyric acid concentration was lower (2.70 g kg−1 DM versus 5.94 g kg−1 DM) (p < 0.05). The lactic acid concentration of silage inoculated with L. rhamnosus HT1 (92.0 g kg−1 DM) was significantly higher than that inoculated with L. plantarum YM3 (57.3 g kg−1 DM) and the CK (69.5 g kg−1 DM) (p < 0.05). For most undesirable bacterial species, such as Stenotrophomonas, Providencia, Paenalcaligenes, Myroides, and Alcaligenes, the relative abundances in the silage ensiled for 60 d were generally higher than in those ensiled for 15 and 30 days. The relative abundance of harmful bacteria in oat silage was higher than that in Italian ryegrass silage. The relative abundances of Stenotrophomonas and Providencia in the CK treatment were higher than those in the silage inoculated with L. plantarum YM3 and L. rhamnosus HT1. The addition of lactic acid bacteria (LAB) helped to inhibit the increase in the relative abundance of harmful bacteria. Therefore, when silage has to be exposed to air, this study recommends that Italian ryegrass be inoculated with Lactobacillus rhamnosus HT1 and used within 15 days of ensiling.